1992
DOI: 10.1002/cne.903250203
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic connections of the narrow‐field, bistratified rod amacrine cell (AII) in the rabbit retina

Abstract: The synaptic connections of the narrow-field, bistratified rod amacrine cell (AII) in the inner plexiform layer (IPL) of the rabbit retina were reconstructed from electron micrographs of continuous series of thin sections. The AII amacrine cell receives a large synaptic input from the axonal endings of rod bipolar cells in the most vitreal region of the IPL (sublamina b, S5) and a smaller input from axonal endings of cone bipolar cells in the scleral region of the IPL (sublamina a, S1-S2). Amacrine input, loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

27
473
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 337 publications
(500 citation statements)
references
References 52 publications
27
473
0
Order By: Relevance
“…(Famiglietti and Kolb, 1975;Kolb 1979;Kolb and Famiglietti 1974;Strettoi et al, 1990Strettoi et al, , 1992. The synaptic input from rod bipolar cells is located at the arboreal dendrites in sublamina b of the IPL.…”
Section: The Aii Amacrine Cell In the Mammalian Retinamentioning
confidence: 99%
See 4 more Smart Citations
“…(Famiglietti and Kolb, 1975;Kolb 1979;Kolb and Famiglietti 1974;Strettoi et al, 1990Strettoi et al, , 1992. The synaptic input from rod bipolar cells is located at the arboreal dendrites in sublamina b of the IPL.…”
Section: The Aii Amacrine Cell In the Mammalian Retinamentioning
confidence: 99%
“…The synaptic input from rod bipolar cells is located at the arboreal dendrites in sublamina b of the IPL. At the EM level, the presynaptic elements are classical ribbon synapses (Kolb 1979;Sterling et al, 1988;Strettoi et al, 1990Strettoi et al, , 1992. The synaptic input is mediated by iGluRs of the AMPA-type (GluARs) (Singer and Diamond, 2003;Singer et al, 2004;Veruki et al, 2003 and immunocytochemical studies have identified the presence of GluA2/3 and GluA4 AMPA receptor subunits postsynaptically (Ghosh et al, 2001;Li et al, 2002).…”
Section: The Aii Amacrine Cell In the Mammalian Retinamentioning
confidence: 99%
See 3 more Smart Citations